Advances and challenges in the management of advanced fibrosis in nonalcoholic steatohepatitis. (November 2018) - Sayiner, Mehmet; Lam, Brian; Golabi, Pegah; Younossi, Zobair M.
Nonalcoholic fatty liver disease (NAFLD) is rapidly becoming the most common type of chronic liver disease worldwide. From the spectrum of NAFLD, it is nonalcoholic steatohepatitis (NASH) that predominantly predisposes patients to higher risk for development of cirrhosis and hepatocellular carcinoma. There is growing evidence that the risk of progression to cirrhosis and hepatocellular carcinoma is not uniform among all patients with NASH. In fact, NASH patients with increasing numbers of metabolic diseases such as diabetes, hypertension, visceral obesity and dyslipidemia are at a higher risk of mortality. Additionally, patients with higher stage of liver fibrosis are also at increased risk of mortality. In this context, NASH patients with fibrosis are in the most urgent need of treatment. Also, the first line of treatment for NASH is lifestyle modification with diet and exercise. Nevertheless, the efficacy of lifestyle modification is quite limited. Additionally, vitamin E and pioglitazone may be considered for subset of patients with NASH. There are various medications targeting one or more steps in the pathogenesis of NASH being developed. These drug regimens either alone or in combination, may provide potential treatment option for patients with NASH.